TRADITION, REPETITION, TRANSFORMATION : The Dynamic of Cultural Globalization - Piliang, Yasraf A. (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2008)
'Tradition' is a contradictory concept with strong ideological burdens. On the one hand, the concept strongly connotes 'repetition', 'fixity' and 'changelessness'; on the other hand, it is diametrically opposed to the concept of 'change', 'dynamism' and 'transformation'. As a form of repetition, tradition is seen as an opposite of change, because it only repeats what 'has been'. However, through a comprehensive interpretation of the concept, it can be argued that the concept of tradition can connote both 'repetition' and 'change'. As a form of repetition, tradition is not totally separated from and immune to a particular pace of change,  innovation or even transformation. This is because there is not only a  'static repetition', but also a 'dynamic repetition' that produces change and difference. Here, I want to stress a 'transformation of tradition'. There are several ways through which a tradition can be  transformed: 1)  reinterpretation of particular forms of tradition; 2) transaesthetics discourse as a dialogues between tradition and other cultures; 3) cultural exchange as a complex process of exchange and selection; 4) critical openness as an inclusive attitude to external cultures; and 5) knowledge differentiation as the enhancement of knowledge of a tradition.